1990
DOI: 10.1111/j.1469-8137.1990.tb00462.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of long‐term open‐air fumigation with SO2 on a field crop of broad bean (Vicia faba L.)

Abstract: SUMMARYEfTects of SO., on growth and production of broad bean, observed in three open-air fumigation experiments, were interpreted in terms of damage components with a mechanistic simulation model. The model consisted of an elementary model for crop growth, extended with submodels for the microclimate in the crop and with a submodel for uptake of SO.^ by leaves and for efTects on leaf photosynthesis.The major part of the observed reduction in total dry matter production could be explained by leaf injury observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The fate of the airborne sulphur was analysed by relating the difference in accumulated sulphate-S to the difference in total-S between control and fumigated plants. The near 1:1 relationship indicates that only a very small amount of S0 2 was converted into organic sulphur, because it was shown in an earlier paper (Kropff, 1990) that the simulated uptake of sulphur from the air by the fumigated plants was close to the observed difference in sulphur content of the fumigated and control plants (Fig. 3).…”
Section: Plant Growth and Crop Productionmentioning
confidence: 96%
See 4 more Smart Citations
“…The fate of the airborne sulphur was analysed by relating the difference in accumulated sulphate-S to the difference in total-S between control and fumigated plants. The near 1:1 relationship indicates that only a very small amount of S0 2 was converted into organic sulphur, because it was shown in an earlier paper (Kropff, 1990) that the simulated uptake of sulphur from the air by the fumigated plants was close to the observed difference in sulphur content of the fumigated and control plants (Fig. 3).…”
Section: Plant Growth and Crop Productionmentioning
confidence: 96%
“…Similiar effects on leaf area and dry matter production were observed in two preceding experiments conducted in 1985 and 1986 at the same location (Kropff et al, 1989a,b). Simulation analysis demonstrated that so2 effects on total dry matter production in all three experiments were mainly caused by the reduction of the green leaf area in the fumigated plots at the end of the growing period (Kropff, 1990) so2 effects on ionic composition Nitrate was not detected in any of the samples. Nitrogen fixation in the nodules appeared to be the most important nitrogen source, because about 450 kg N ha-t was taken up by the plants (1985 experiment at the same conditions), whereas only 50 kg nitrate-N ha-t and 68 kg ammonium N ha-t was available from the potting mixture and fertilizer.…”
Section: Plant Growth and Crop Productionmentioning
confidence: 99%
See 3 more Smart Citations